Mandible Fractures - Pickrell, Brent B.; Serebrakian, Arman T.; Maricevich, Renata S. (Seminars in Plastic Surgery, 2017)
Mandible fractures account for a significant portion of maxillofacial injuries and the evaluation, diagnosis, and management of these fractures remain challenging despite improved imaging technology and fixation techniques. Understanding appropriate surgical management can prevent complications such as malocclusion, pain, and revision procedures. Depending on the type and location of the fractures, various open and closed surgical reduction techniques can be utilized. In this article, the authors review the diagnostic evaluation, treatment options, and common complications of mandible fractures. Special considerations are described for pediatric and atrophic mandibles.
Keywords: mandibular fracture; occlusion; facial trauma; open reduction; maxillomandibular fixation